Vous êtes sur la page 1sur 6

# Homework1

## Math Homework Help | Math Homework Help Service

Homework1
3422 SW 15 Street
Suite #8924
Deerfield Beach, FL, US 33442
Tel: +1-626-472-1732
Web: https://homework1.com/
Email: info@homework1.com
Pinterest: https://www.pinterest.com/homeworkone/

Homework1
At Homework1.com we offer authentic and 100% accurate
online homework help and study assistance to students from
USA, UK, Australia, and Canada. However, we dont offer
students only academic assignment help service to complete
their study project; rather we offer our best effort to teach our
student-clients about the assignment we have solved. Our
tutors are not only subject matter experts, they are avid
student-mentors and are ready to walk extra miles to make
them understand the fundamentals of the assignment done,
and help them to learn the solution by heart.
We are available online by 247 and we can be reached via email, live chat, as well as
by direct phone calls. Our USP is quick turnaround time with stringent quality assurance
about the assignment we undertake. We offer assistance is writing dissertations,
academic and project related essay writing, and in writing and reviewing research
papers. These research papers are done by best subject matter experts available and we
offer 100% plagiarism free content by following proper and prescribed house style.
Do you want to get higher score in mathematics in exam? In both the cases your math
assignments have to be completed with 100% accuracy and within deadline, which
sometimes you may not find manageable. In these cases you might have thought to give
up! But actually you still can be right on track and win the situation because we are here
to support you with our expert math homework help!

Illustration: 1

## (i)x(x +1) + 8 = (x +2) (x+3) (ii) x (x+6) = 0 (iii) x +

(iv) 4x2 + 6x + 1 =x2 + 2x + 3 (v) x2 +

1
2

=1, x 0

= 2, x 0

Solution:
(i) x (x+1) + 8 = (x+2) (x+3)
= x2 + (x+1) + 8 = x2 +2x +3x + 6
= 4x -2 = 0 = 2x -1 = 0, which is linear, given equation is not quadratic.
(ii) x(x+6) =x2 + 6x = 0, which is a quadric equation
(iii) X +

=1=

(v) x2 +

=2=

## = + 1 = 2x2 = x4 -2x2 + 1 =0.

Homework1
( 4 +2 2 + 1 is a polynomial of degree 4)

## Which is not a quadratic equation

Illustration: 2
For the quadratic equation, determine whether the given value of x is
a solution of the given quadratic equation or not. (i) 3x2-x-1 =0 ; x = -1
(ii) 6x2 +
7x-5 = 0; x =

## (iii) x2+2x-2 = 0 ; x = 3 1 and

3+1

Solution:
Putting x = -1 on the left hand side of the given equation, we get
L.H.S = 3(1)2 - (-1) = 3 + 1-1 =3 0 = 3 2 +4X -2 =0
x = -1 is not a root of the given equation
(ii) Putting x =
L.H.S = 6

1
2

on the left hand side of the left hand side of the given equation, we get

2+7

x=

1
2

-5 = 6

-5=

= 0 = R.H.S.

## is a root of the given equation.

(iii) Putting x =

## 3 -1 on the left hand side of the given equation, we get

L.H.S = ( 3 1)2 + 2

3 1 -2 = 3 +1 -2 3 + 2 3 -2 -2

## = 4 -4 = 0 = R.H.S x = 3 + 1 is not a root of the given equation.

Homework1
Again putting x = 3 + 1 on the left hand side of the given equation, we get
L.H.S =( 3 + 1)2 + 2

3 + 1 -2 = 3 +1 +2 3 + 2 3 -2 -2

Illustration: 3
3x2-kx-2 = 0

## Find the value of k so that x = 2 is root of the quadratic equation

(A.I.C.B.S.E.2002)
Solution:
Since 2 is root of the equation 3x2 kx= 0 3(2)2 - k(2)-2 =0
= 12-2k-2 = 0 = 2k = 10 and k =5

Illustration: 4 If one root of the equation 2x2 + px 15 = 0 is -5, find the value of p.
( C.B.S.E 2012)
Solution:
Since 2 is root of the equation 2x2 + px 15 = 0 2 (-5)2 + p (-5) -15 = 0= 50 5p
15 = 0 = 5p = 7

Homework1

Illustration:5
2 5 + 6 +

## Check, whether 3 is root of the equation.

2 9 = 4 2 14 + 16

Solution:
Putting x = 3, on the L.H.S, we get
32 5(3) + 6 + 32 9 = 9 9 = 0 + 0 = 0
R.H.S =

3(3)2 14(3) + 16 = 36 42 + 16 =

62 42 = 10

Illustration: 6
(a) X2 +

= 1, x 0 (b) x +

Solution:
(a) +

= 1,

= x3 + 1 =x

= x3 x + 1 = 0

(b) x +

(a) holds.

Homework1

Illustration: 7

## Which of the following is a quadratic equation.

(a) X2 + 2x + 1 = (4-x)2 + 3

## (d) 3 -x2 = (x-1)3

(c)(K+1) x2 + 2x = 7, where, k = -1
Solution:
Clearly (d) holds.
Sol. Clearly (d) holds.